Entrepreneurial behaviour : unveiling the cognitive and emotional aspects of entrepreneurship - Caputo, Andrea; Pellegrini, Massimiliano M. (Entrepreneurial behaviour, 2020)
The success, longevity, and survival of SMEs are deeply linked to the effectiveness of individual decision-making processes, and established firms need to develop an entrepreneurial and innovative decision-making processes to maintain competitive advantages in a continuously changing and increasingly turbulent environment.